2016
DOI: 10.4028/www.scientific.net/msf.874.279
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Investigation of Ultrasonic Assisted Pulsed Electrochemical Grinding of Ti-6Al-4V

Abstract: Aiming at the development of a novel grinding technology for the highly efficient machining of difficult to machine materials such as Ti-6Al-4V, an ultrasonic assisted pulsed electrochemical grinding (UAECG) method was proposed. The current work is to reveal the fundamental grinding characteristics of the UAECG of Ti-6Al-4V by experimentally investigating the effect of vibration amplitude on grinding forces, actual material removal and work-surface roughness under different process parameters such as the input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…According to their structural features and machining modes, machine tools are classified into vertical and horizontal. In previous research on UAECG [ 5 , 7 , 8 , 9 , 18 ], very small lightweight conductive grinding wheels and integrated ultrasonic electric spindles were used; the conductive grinding wheel on-machine dressing was not considered, and all machine tools were all vertical structures. For the ICUAECG, a large conductive grinding wheel and ordinary grinding electric spindle are used, the ultrasonic vibration system needs to be installed, the volume and weight of the grinding electric spindle and conductive grinding wheel are large, and considering the conductive grinding wheel on-machine dressing, the horizontal structure is appropriate for the special machine tool.…”
Section: Structural Design Of Special Machine Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…According to their structural features and machining modes, machine tools are classified into vertical and horizontal. In previous research on UAECG [ 5 , 7 , 8 , 9 , 18 ], very small lightweight conductive grinding wheels and integrated ultrasonic electric spindles were used; the conductive grinding wheel on-machine dressing was not considered, and all machine tools were all vertical structures. For the ICUAECG, a large conductive grinding wheel and ordinary grinding electric spindle are used, the ultrasonic vibration system needs to be installed, the volume and weight of the grinding electric spindle and conductive grinding wheel are large, and considering the conductive grinding wheel on-machine dressing, the horizontal structure is appropriate for the special machine tool.…”
Section: Structural Design Of Special Machine Toolmentioning
confidence: 99%
“…For UAECG, Wu et al [ 5 , 7 , 18 ] developed an ultrasonic-assisted electrochemical mill-grinding vertical machine tool by installing an ultrasonic electric spindle on a 3-axis NC machine tool. They studied the planar ultrasonic-assisted electrochemical mill-grinding of Ti-6Al-4V with a metal-bonded CBN grinding wheel of 1.8 mm in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…S.S. Li, et al was conducted to compare and analyze the difference in cutting force of workpieces between UAECG technology and ultrasonic-assisted pulse electrochemical grinding processing technology. The results showed that the normal stress and tangential stress of ultrasonicassisted electrochemical grinding are respectively reduced by about 57% and 56% in comparison with that of traditional grinding [20][21][22].…”
Section: Introductionmentioning
confidence: 96%
“…However, there existed many defects for traditional processing methods such as low processing efficiency, serious tool wear, high frictional heat and residual stress, which were hardly beneficial for the processing of difficult-to-machine materials. A series of new processing technologies were thus proposed such as laser processing, electric discharge processing, electrochemical processing and high-speed water jet processing [3][4][5]. Generally, nontraditional machining exhibits many advantages such as high machining efficiency and accuracy, low tool wear and low frictional heat [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al proposed an ultrasonic-assisted pulse electrochemical grinding method. The influence of vibration amplitude on grinding force, material removal rate and workpiece surface roughness under different machining parameters such as applied voltage and rotating speed was studied [ 30 ].…”
Section: Introductionmentioning
confidence: 99%